AVALIAÇÃO MICROBIOLÓGICA DE PASTÉIS COMERCIALIZADOS NA CIDADE DE SANTA ROSA/RS - FACHINA, CLÁUDIA R.; SPENGLER, CAMILA; PASCH, JOCIANE F.; STEFANELLO, RICHELI A.; YOSHIDA, SAYURI; FIORENTINI, ÂNGELA M. (Salão do Conhecimento, 2013)
Resumo